New species of Pachytriton (Caudata: Salamandridae) from the Nanling Mountain Range, southeastern China - Wu, Yunke; Wang, Yuezhao; Hanken, James (Zootaxa, 2012)
New species of amphibians are being reported at an astonishingly fast rate. These include some that have been known tothe commercial pet trade for years but have not been formally described due to uncertain origin. The distinctive phenotypeof “Pachytriton B” among the Chinese stout newts (also known as paddle-tailed newts) is one such example. Throughexamination of museum specimens, we locate a population from Mt. Mang within the Nanling Mountain Range with mor-phology and coloration similar to Pachytriton B. Molecular phylogenetic analyses strongly suggest that this populationand Pachytriton B belong to the same species, which differs from congeners morphologically and chromatically and isdescribed here as a new species. This species is characterized by a large and stout body, uniformly light brown dorsum,and orange spots or blotches that extend ribbon-like along the dorsolateral sides of the body. A mitochondrial genealogysuggests that the new species is the sister taxon to the group (P. brevipes + P. feii). Morphologically, this species is significantly stouter than P. feii and has significantly longer limbs than P. brevipes.